Atrial Fibrillation: a Marker or Risk Factor for Stroke - B. A. Tatarsky; D. A. Napalkov (Рациональная фармакотерапия в кардиологии)
Atrial fibrillation (AF) is strongly associated with stroke risk, but an association by itself does not necessarily imply causation. The question remains whether AF is a risk factor for stroke and whether treatment that reduces the severity of AF will also reduce the burden of stroke. On the other hand, it is possible that AF is a risk marker associated with atrial insufficiency, in which structural and electrical atrial remodeling coexist, leading  to the clinical manifestations of AF and the risk of stroke simultaneously. Atrial fibrillation and stroke are inextricably linked to the classic Virchow pathophysiology, which explains thromboembolism as blood stasis in a fibrillating left atrium. This concept has been reinforced by the proven efficacy of oral anticoagulants for the prevention of stroke in AF. However, a number of observations showing that the presence of AF is neither necessary nor sufficient for stroke cast doubt on the causal role of AF in vascular brain injury. The growing recognition of the role of atrial cardiomyopathy and the atrial substrate in the development of stroke associated with AF, as well as stroke without AF, has led to a rethinking of the pathogenetic model of cardioembolic stroke. A number of recent studies have shown that AF is a direct cause of stroke. Studies in which cardiac implantable devices have been used to collect data on pre-stroke AF do not appear to show a direct time relationship. The presence of AF is neither necessary nor sufficient for stroke, which casts doubt on the causal role of AF in cerebrovascular injury. Known risk factors for stroke in the presence of AF are also recognized risk factors for ischemic stroke, regardless of the presence of AF. The risk of stroke in patients with AF in the absence of risk factors differs little from that in patients without AF. This work is devoted to an attempt to answer the question whether AF is a marker or a risk factor for ischemic stroke.